Deconstructing Nepali National Symbols: Contestation and Reconciliation in Indigenous Poetry - Rai, Prakash (Curriculum Development Journal, 2024)
Indigenous poetry articulates Indigenous communities’ voices deeply rooted in oral culture, mythic narratives, and traditions, reviewing the dominant national identity and culture. In this backdrop, the paper analyzes Shrawan Mukarung’s “An Autography of 98” Bhupal Rai’s “The Caste System of Water”, Bhogen Ekle’s “A Request”, and Sushma Ranahma’s “Adivasi”(Aborigine) poems to examine how they redefine Nepali national identity and symbols for an inclusive nationalism. In doing so, the study has employed the qualitative method, specifically a textual analysis based on the theories of Nationalism by Benedict Anderson, and David Stevens for theoretical tools and Cultural psychology by Kitayama, Cohen, and Shweder as the conceptual framework. The research unveils that national identity and nationalism framed by the dominant Hindu ideology marginalized the ethnic indigenous culture and tradition and the poetry voices for an inclusive approach to national identity and symbols. The study further concludes that Indigenous poetry not only challenges the mainstream national identity, symbols, and nationalism but also seeks to reconcile people-centric nationalism. Inclusive nationalism unites people and cultures from diverse socio-cultural and economic backgrounds to form an equitable and just society. The research has significant implications—bringing awareness to reframe the new national symbols and identities, aiding researchers and academicians for further study in the discipline and paving the way for policymakers and planners to see the potential of diversity from new perspectives.